(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: The frequency and efficacy of absorbable and non-absorbable sutures in the treatment of traumatic surgical wounds are investigated in this study. In order to maximize suture selection for better clinical outcomes and fewer issues, it assesses their effects on healing, cosmetic results, and patient satisfaction. Objective: To determine the prevalence of cosmetically absorbable and non-absorbable sutures in the management of traumatic surgical wounds. Methodology: This was a randomized control trial carried out at Services Hospital duration of six months and using a calculated sample size of 80 based upon two means of suture infection. Patients aged 20–50 with traumatic surgical wounds in aesthetically sensitive areas such as the face, neck, or hands, in which the cosmetic outcomes were prominent. Results: The study analyzed 80 participants, with 53.8% aged 20–30, 43.8% aged 31–40, and 2.5% aged 41–50. Males comprised 57.5%, females 40.0%, and 2.6% were unspecified. Lacerations were the most common wound type (56.3%), followed by puncture wounds (32.5%) and abrasions (11.3%). Upper extremities were the most affected (46.3%), followed by the head and face (41.3%) and lower extremities (12.5%). Both absorbable and non-absorbable sutures were used equally. No significant correlation was found between suture type and scar appearance (p=0.243) or healing time (p=0.686). However, non-absorbable sutures were associated with significantly higher satisfaction levels (p=0.002). Conclusion: The study found that both absorbable and non-absorbable sutures were equally used in managing traumatic surgical wounds. No significant correlation was observed between suture type and scar appearance (p=0.243) or healing time (p=0.686). However, patient satisfaction significantly favored non-absorbable sutures (p=0.002), with recipients reporting higher levels of happiness compared to those with absorbable sutures.